Hijab, Normativitas Agama, dan Female Agency dalam Antropologi Sosial dan Fikih Islam: Eksplorasi Etnografis Praktik Hijab Kontekstual di Kalangan Mahasiswi Universitas Hasanuddin - Sari, Fitria Dwi Ambar; Yahya, Yahya; Basir, Muhammad (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
The hijab is regarded in Islamic jurisprudence as a religious obligation for Muslim women. However, within contemporary social contexts, its practice has increasingly become a site of negotiation between religious normativity, individual agency, and socio-cultural influences. This study examines contextual hijab practices among female students at Hasanuddin University by exploring how they interpret, negotiate, and perform the hijab in everyday life through the perspectives of social anthropology and Islamic jurisprudence. This research employed a qualitative ethnographic approach to capture the lived experiences of participants within their natural social environment. Data were collected through in-depth semi-structured interviews, participant observation, and field notes involving fourteen female students at Hasanuddin University who demonstrated contextual or inconsistent hijab practices. The data were analyzed using thematic analysis, integrating anthropological concepts of agency and identity with Islamic jurisprudential perspectives on religious obligations. The findings reveal that contextual hijab practices emerge from the dynamic interaction between religious commitment, personal autonomy, peer influence, fashion trends, campus culture, and family expectations. Participants did not generally reject the normative religious status of the hijab; instead, they continuously negotiated its implementation according to particular social settings and personal circumstances. These practices illustrate that female agency operates not as resistance to religion but as an adaptive process through which religious norms are interpreted and embodied within diverse social contexts. The study also found that participants experienced varying forms of social response, ranging from acceptance and indifference to moral judgment and stigmatization. Contextual hijab practices among female students demonstrate that the hijab functions simultaneously as a religious obligation, a cultural symbol, and a marker of personal identity. Integrating social anthropology with Islamic jurisprudence provides a more comprehensive understanding of how religious normativity and female agency coexist through continuous negotiation within contemporary Muslim society.